2019
DOI: 10.15408/ajme.v1i1.11687
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Pemecahan Masalah Pada Materi Pokok Bangun Ruang Sisi Datar

Abstract: Tujuan penelitian ini adalah untuk menganalisis apa saja kesalahan siswa dalam mengerjakan soal permecahan masalah materi pokok bangun ruang sisi datar, serta apa saja yang menyebabkan kesalahan siswa dalam mengerjakan soal pemecahan masalah materi pokok bangun ruang sisi datar. Pengambilan subyek penelitian yaitu dari 38 siswa kelas VIII-B yang mengikuti tes, hasil tes siswa diurutkan berdasarkan dari nilai yang terbesar ke yang terkecil kemudian dibagi menjadi tiga kelompok. Subyek penelitian terdiri dari 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
2
2
0
2
Order By: Relevance
“…Students do not understand and apply the concept of triangle prerequisites. This is in line with the opinion [9] which says that students experience a lack of understanding in the concept of flat wake.…”
Section: Here Are the Results Of The Test And Interview Answerssupporting
confidence: 89%
See 1 more Smart Citation
“…Students do not understand and apply the concept of triangle prerequisites. This is in line with the opinion [9] which says that students experience a lack of understanding in the concept of flat wake.…”
Section: Here Are the Results Of The Test And Interview Answerssupporting
confidence: 89%
“…In solving the questions given by the teacher, students still experience some errors [8]. Errors in solving problems are errors made by students because they only work on one or two questions from several stages of problem solving or are not in accordance with the problem solving steps [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the research results, information was obtained that there is a tendency for students to experience learning obstacles due to being careless in learning or other things psikological ontogenic. The results of this research are in line with (Atiqoh, 2019) which revealed that students were less careful when carrying out calculations and did not double-check their answers. In learning, students tend to be careless and not careful, which causes students' low ability to solve mathematical problems (Jannah, 2023).…”
Section: Resultssupporting
confidence: 82%
“…Several studies have noted that most students still have difficulty understanding geometric concepts (Bustang, Zulkardi & Darmawijoyo, 2013;Fauzi, 2019;MdYunus & Suraya, 2019). Plane figures are among the concepts where students make numerous mistakes in solving problems; these mistakes are made because students lack practice and do not understand the concept of the problem (Atiqoh, 2019). Consequently, there is a need for a solution using a cognitive approach in the form of task variations.…”
Section: Introductionmentioning
confidence: 99%